PUNCAK-PUNCAK CAPAIAN KAUM SUFI - Saude, Saude (Institut Agama Islam Negeri (IAIN) Palu, 2006)
Mysticism is a particular method of approaching God, making use of intuitive and emotional spiritual faculties that are generally dormant and latent unless called into play through training under guidance. Throughout history of sufism, we have known some great sufis such as al-Ghazali, Rabiâah al-Adawiyah; Abu Yazid al-Bustami, and Husain ibn Mansur al-Hallaj. However, they employed different terms for their inner experiences. It is within this context that this article tries to elaborate their spiritual experiences and how to express them in the state of ecstasy.Kata Kunci: Sufi, tasawuf, maqamat